Higher Education Students’ Perception of Online Shopping Post-COVID-19 - C, Anjali Devi (Journal of Global Economy, Business and Finance, 2025)
During COVID-19, due to lockdown most of the people shift offline shopping to online shopping where multiple options are exist for the similar kind of product. People found that the online shopping way more comfortable than offline shopping& online purchasing product delivery &return process is very good and easy to use it compare to offline shopping.